2022
DOI: 10.3390/soilsystems6010009
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Biosolids Application on Land: Beneficial Recycling of Nutrients or Eutrophication of Agroecosystems?

Abstract: The impact of repeated application of alkaline biosolids (sewage sludge) products over more than a decade on soil concentrations of nutrients and trace metals, and potential for uptake of these elements by crops was investigated by analyzing soils from farm fields near Oklahoma City. Total, extractable (by the Modified Morgan test), and water-soluble elements, including macronutrients and trace metals, were measured in biosolids-amended soils and, for comparison, in soils that had received little or no biosoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Some studies have determined that Zn may be more biologically available and mobile in soils treated with sludge 28 . McBride 29 also showed that adding biosolids to soil can increase the fraction of bioavailable Zn. This mobility has been observed to increase with time after sewage sludge addition to the soil since it can form soluble chelates with humified and non-humidified forms of organic matter 28 .…”
Section: Resultsmentioning
confidence: 98%
“…Some studies have determined that Zn may be more biologically available and mobile in soils treated with sludge 28 . McBride 29 also showed that adding biosolids to soil can increase the fraction of bioavailable Zn. This mobility has been observed to increase with time after sewage sludge addition to the soil since it can form soluble chelates with humified and non-humidified forms of organic matter 28 .…”
Section: Resultsmentioning
confidence: 98%
“…The P solids recovered from the EPRC can be comparable to phosphate rock, making it suitable to be a feedstock for conventional wet phosphoric acid processes or as solid P fertilizers for tropical acid soils. , Recent studies found that long-term application of biosolids (whole digestate after dewatering) on land could result in an excessive P concentration in surface soils, contributing to nonpoint source P contamination and eutrophication in aquatic environments. , Thus, the P products containing consistent P contents (28.42–33.51% as P 2 O 5 ) will enable more accurate P resource management. In addition, the P production rate, heavy metal contents, and the distribution of P products in the ENRC are controllable, making it a versatile technology that will be applicable to other P-abundant solid wastes such as livestock manure.…”
Section: Resultsmentioning
confidence: 99%
“…Padeyanda et al [56] found a very high EP value for Composting (Not Specified), more than 7 kg PO 4 3− eq/t of food waste, due to the high NH 3 emission during the composting process. The eutrophication category is more affected by excess nutrients derived from nitrogen and phosphorus, that in high concentrations in organic waste to be composted, can affect the ecosystem with eutrophication [88]. Another aspect that can increase the EP results is considering the high concentration of nutrients from the wastewater generated on composting piles and often leachate into the soil [33].…”
Section: Results and Their Interpretationmentioning
confidence: 99%